Multivariate analysis in yellow inbred lines of Maize (Zea mays L.) (Bangladesh Journal of Agricultural Research, 2015)
Twenty five yellow inbred lines of normal maize were evaluated for eleven parameters to study the genetic divergence using Mahalonabiss D2 and Rao s canonical variate analysis. The twenty five inbreds fell into five distinct clusters. The intra-cluster distance in all the five clusters was more or less low, indicating the genotypes within the same clusters were closely related. The highest intercluster distance was observed between cluster I and VI and the lowest between the cluster II and III. The cluster IV and V each contained the highest number of genotypes. Cluster V showed the highest mean values for kernel yield and all the yield contributing traits except 1000-kernel weight and cluster II had the lowest mean values for plant and ear height and maturity characters. Days to silking, ear length, number of kernels/row, 1000-kernel weight and kernel yield showed maximum contribution towards total divergence among different characters. Based on medium to high inter-cluster distances, per se performances and desirable traits, fourteen yellow inbred lines viz. BIL 77, BIL 97, CML 287, CML 470, CML 480, CML 486, CZ 2370-22-2, CZ 2370-24-3, CZ 2370-28-2, CZ 23 70-31-3, IPB 911-2, IPB 911-22, IPB 911-36 and IPB 911-50 were selected for future hybridization program. Crossing between these genotypes have the chance to obtain higher heterosis with high performing crosses. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22531 Bangladesh J. Agril. Res. 39(4): 553-561, December 2014